Phytochrome and Phytohormones: Working in Tandem for Plant Growth and Development - Lymperopoulos, Panagiotis; Msanne, Joseph; Rabara, Roel (Frontiers in Plant Science, 2018)
Being sessile organisms, plants need to continually adapt and modulate their rate of growth and development in accordance with the changing environmental conditions, a phenomenon referred to as plasticity. Plasticity in plants is a highly complex process that involves a well-coordinated interaction between different signaling pathways, the spatiotemporal involvement of phytohormones and cues from the environment. Though research studies are being carried out over the years to understand how plants perceive the signals from changing environmental conditions and activate plasticity, such remain a mystery to be resolved. Among all environmental cues, the light seems to be the stand out factor influencing plant growth and development. During the course of evolution, plants have developed well-equipped signaling system that enables regulation of both quantitative and qualitative differences in the amount of perceived light. Light influences essential developmental switches in plants ranging from germination or transition to flowering, photomorphogenesis, as well as switches in response to shade avoidances and architectural changes occurring during phototropism. Abscisic acid (ABA) is controlling seed germination and is regulated by light. Furthermore, circadian clock adds another level of regulation to plant growth by integrating light signals with different hormonal pathways. MYB96 has been identified as a regulator of circadian gating of ABA-mediated responses in plants by binding to the TIMING OF CAB EXPRESSION 1(TOC1) promoter. This review will present a representative regulatory model, highlight the successes achieved in employing novel strategies to dissect the levels of interaction and provide perspective for future research on phytochrome-phytohormones relationships toward facilitating plant growth, development, and function under abiotic-biotic stresses.